ENFERMEDAD DE BUERGER - Cascante Quirós, Ana Yanci (2011)
Thromboangiitis obliterans also known asBuerger’s Disease is a segmental, inflammatory,occlusive, non-atherosclerotic disease that involves small and medium caliber arteries, veinsand nerves; affects mainly young males withtobacco abuse history.The clinical presentation is caused for the occlusion and stenosis of the distal vasculature in upper and lower limbs. The initial ischemicsymptoms are intermittent claudication in theaffected extremities. In the natural history of thedisease, patients can present severe ischemia ofthe limbs (rest pain, ulcers, and digital gangrene).Arteriographic studies show a pattern of abruptocclusion of the distal vasculature, with areas ofnormal vessels between the affected segments,with intense tortuosity in the recanalized segments described in a “corkscrew shape”. Thehistology varies according to the phase of thedisease but usually and occlusive intraluminalthrombus with lymphocytes, giant cells, inflammation of the media and the adventitia with aninternal elastic lamina unaffected. The key oftreatment is to eliminate the smoking but alsosome pharmacologic and surgical approacheshave been established as well as new therapiesunder trials.